Perubahan Susunan Anggota Direksi dalam Ruang Lingkup Hukum Perusahaan - Febriana Rahmadhani (UNES Law Review, 2023)
Law Number 40 of 2007 concerning Limited Liability Companies provides that the Board of Directors is a company organ with authority and full responsibility for managing the company for the interests of the company in accordance with the company's aims and objectives, as well as representing the company, both inside and outside the court in accordance with the provisions articles of Association. Just as humans who have organs that are subject to the will of the human brain, the analogy is that directors often appear as the personification of the legal entity itself, namely a Limited Liability Company with the limitation that the scope of the business established must not conflict with morality, public order and statutory regulations. invitation. In Indonesia, in general the responsibilities of directors are divided into two stages, namely before the Limited Liability Company obtains status as a legal entity and after the Limited Liability Company obtains status as a legal entity. In relation to the composition and number of directors in a company, generally it consists of one director. Procedures for nominating, appointing, replacing (changing) and dismissing members of the board of directors are regulated in the articles of association of a company. GMS decisions regarding the appointment, replacement and dismissal of members of the board of directors should determine when the appointment, replacement and dismissal of one or more members of the board of directors will come into effect. If the appointment of the director is the first director, then the appointment must be stipulated in the deed of establishment. As a result of the legal consequences of not including the first director in the deed of establishment, the Minister can declare that the establishment of the company is invalid according to law. This research was conducted using normative juridical research methods.